Personal Loan Agreement Between Small Traders and “Bank Plecit” at Traditional Market Banyumas, Central Java; A Study from the Perspective of Moral Judgement - Ratna Kartikawati; Zuraini Jamil Osman (Kosmik Hukum, 2021)
In Indonesia, it has found that small traders are still borrowing money from ‘bank plecit’ or known as loan shark although they know the risks of borrowing money from them. This happens because they are financially desperate and very little documentation is required. This study aims to explore the experiences and understandings (cognitive) of small traders and ‘bank plecit’ at Traditional Market, Bayumas, Jogjakarta from the moral judgement perspective that has influenced their personal loan agreement process. Seven ‘bank plecit’ and nine small traders from Traditonal Market, Bayumas, Puworkerto were selected for this study. A qualitative approach using one to one in-depth interview method and observation were used to gather the primary data. The findings show that small traders have a clear understanding of the risk of paying a high-interest rates when they decided to borrow money from ‘bank plecit’.  Several reasons are given by both group of respondents in the area of moral judgement decision-making based on a cognitive view that can be considered as internal and external factors. For the small traders, the internal factors are related with them such as responsibility to family so that they can get out of the financial crisis easily and belief in God when they surrender with their life's hardships. While external factors show that small traders believe that it’s a rational decision because the loan process and procedures from the ‘bank plecit’ is often faster and easier than the legal banks that they considered as so straight. They considered that borrowing money from the ‘bank plecit’ was their best rational decision they can made in order to get capital for their business and for their survival. For the ‘bank plecit’, they are only concerned about profits when they agreed to lend the money to small traders, but they said that helping small traders is their responsibility. In addition, they also aware of setting high rate interest to the small traders, they assume that is the way they are helping small traders as the small traders desperately need money. They believed that cognitively, decision that they have made is right because they will help the small traders to start or continue their business. Overall, this study found that moral judgement in cognitive made by both group of respondents are based on their personal situations and lives. Keywords: moral judgement, cognitive, ‘bank plecit’, personal loan agreement